6.4k views
0 votes
-3 square root of 2 + 3 square root of 8

User RodMcGuire
by
5.8k points

1 Answer

7 votes

Answer:


3 √(2)

Explanation:


-3 √(2) + 3 √(8) =

To add or subtract square roots, you must be taking the square roots of the same number. We need to change square root of 8 into a number times square root of 2.


= -3 √(2) + 3 √(4 * 2)


= -3 √(2) + 3√(4) * √(2)


= -3 √(2) + 3 * 2 * √(2)


= -3 √(2) + 6 √(2)

Now that we have two square roots of 2, we add them like we add like terms.


= 3 √(2)

User Glenbot
by
5.7k points